ANALISIS EFEKTIFITAS DAN KONTRIBUSI HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PROVINSI PAPUA - Usman Funangi; Julius Ary Mollet; Charly M. Bisay (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
The purpose of this research is to find and analyze how much the effectiveness of the local asset management and all that will be conducted in order to raise local revenue. Data used is secondary data. Analysis technique using the ratio of effectiveness and the ratio of contribution. The result shows the ratio of effectiveness and the ratio of contributed to local revenue show a fairly good measurement, this can be seen from the the percentage value. Keywords: effectiveness, contribution, local revenue.